2017
DOI: 10.1002/jcb.25867
|View full text |Cite
|
Sign up to set email alerts
|

CsA Promotes XIST Expression to Regulate Human Trophoblast Cells Proliferation and Invasion Through miR-144/Titin Axis

Abstract: In our previous study, we revealed that Cyclosporin A (CsA) could inhibit miR-144 expression to regulate proliferation and invasion of human trophoblast (HT) cells through miR-144 targeting titin. This partially demonstrated the mechanism by which CsA promotes titin expression to increase the vitality of HT cells. However, the mechanism by which CsA inhibits miR-144 expression remains to be investigated. Recently, the interaction between lncRNA and miRNA has been frequently reported to play major role in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…41,42,20 A recent report also showed that CsA exerts specific effects on the inhibition of miR-144 expression to regulate proliferation and the invasion of the human cytotrophoblast and therefore acts as an adjuvant in the vitality of trophoblast cells. 43 Although we have not studied proliferation, the analysis of cellular metabolism by MTT did not show metabolic changes, suggesting that there should be no significant cell death associated with CsA treatment, thereby reinforcing the data from the literature.…”
Section: Discussionsupporting
confidence: 81%
“…41,42,20 A recent report also showed that CsA exerts specific effects on the inhibition of miR-144 expression to regulate proliferation and the invasion of the human cytotrophoblast and therefore acts as an adjuvant in the vitality of trophoblast cells. 43 Although we have not studied proliferation, the analysis of cellular metabolism by MTT did not show metabolic changes, suggesting that there should be no significant cell death associated with CsA treatment, thereby reinforcing the data from the literature.…”
Section: Discussionsupporting
confidence: 81%
“…FOS and 3 other members, FOSB, FOSL1 and FOSL2, belong to the Fos gene family, which encode leucine zipper proteins that dimerize with JUN family proteins. The dimers can form a transcription factor complex with activator protein-1 (AP-1) [48][49][50]. Proteins encoded by Fos genes play an important role in cell differentiation, transformation, proliferation and apoptosis [51][52][53].…”
Section: Agingmentioning
confidence: 99%
“…Certain of these nuclear isoforms of connectins have been implicated as cell cycle promoters 11 , 17 19 . The N-terminal short fragment of connectin was expressed in the nucleus of human osteoblastic cells, and promoted proliferation by activating the Wnt/β-catenin pathway 17 .…”
Section: Introductionmentioning
confidence: 99%